Pre-treated sludge cake filtration characteristics and properties in a cake filtration system - Lee, Wei Jun (2017)
The compatibility of thermal and ultrasonicated pre-treated SBR sludge in a cake filtration system was investigated. Furthermore, examination and analysis on the physical characteristics and filtration properties of the pre-treated sludge as a cake filter medium was conducted. The filtration effectiveness of each pretreated sludge cake layer was quantified by comparing the treatment of effluent water against the cake filtrate (final effluent). 40°C thermally pre-treated sludge, when used as a cake filter medium demonstrated reduced concentrations of COD by 20%, Ammonia by 5.47%, SMP-proteins by 9.2%, SMP-Polysaccharides by 26.25%, Nitrite by 52.69%, Turbidity by 71.75% and TSS by 77.02% in the cake filtrate (final effluent). The cake filtrate also demonstrated turbidity of 0.38 < 1 NTU. The average CST of thermal pre-treated sludge was 6.35seconds while Mili-Q was 6.40seconds, implying similar dewaterability properties. The average filtration lifetime of 240minutes was twice of non-pre-treated sludge, implying reduced need for backwashing. Further analyses were conducted following the initial assessment. Thermal pre-treatment displayed no observable effect on particle size and were analyzed using fluorescence excitation-emission matrix spectroscopy, further revealing that changes to SMP concentration were related to the release of soluble microbial by-product-like and protein-like substances within the domain of SMPs. Despite slightly higher SMP concentrations after pre-treatment, 4.38mg/L to 5.13mg/L and 1.85mg/L to 2.31mg/L, for proteins and polysaccharides respectively, the finale filtrate revealed reduced SMP proteins and polysaccharides concentrations. Additionally, the investigations into fouling mechanisms of the sludge cake surrounding proteins, polysaccharides, lipids and filamentous bacteria demonstrated that increased lipids concentrations were not related to filamentous bacteria and that the fouling mechanism of the thermal pre-treated sludge was dependent on SMPs. The results implied that the thermal pre-treated sludge is effective in functioning as cake filter medium for a cake filtration system.